IEC61850용 게이트웨이 개발 및 성능시험 - 우천희(Chun-Hee Woo); 이보인(Bo-In Lee) (전기학회 논문지 P권, 59(1), 2010)
The IT project for power plants initiated domestically in 2005 necessitates the power equipment facility and the controllers for those to be sufficiently adaptable for automation system for power substations. This implies that the power plants using power equipments must be developed to satisfy the IEC61850 standards. The IEC61850 communication standards that all power equipment and facility and controllers installed in automation system for power substations must follow has had its Parts 3 and Part 4 established as international standard in January 2002 and Part 10 in May 2005, the last to become international standard. Hence all separate parts of the original IEC61850 standard came to be established as international standards. As a consequence, after 2005, in most power substations around the world the IEC61850 standard is being applied and the prominent makers are geared towards manufacturing products to the IEC61850 standard. The IEC61850 is being recognized as an essential standard that must be applied to not only power substations but for automation of power systems and communication systems. In this research, the Gateway device that connects current SCADA system and IEC61580 based system has been domesticated with Korea‘s own technology and extensive testing was carried out in order to obtain confidence in its performance.